2019
DOI: 10.1111/vsu.13212
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between synovial fluid cytokine concentrations and limb function in normal dogs and in dogs with lameness from spontaneous osteoarthritis

Abstract: Objective To determine the relationship between synovial biomarker concentrations and severity of lameness and to assess the ability to differentiate normal from osteoarthritic joints with synovial biomarker concentrations. Study design Prospective clinical study. Sample population Twelve hounds with no evidence of osteoarthritis (OA) and 27 client‐owned dogs with unilateral lameness and joint pain in a single joint from naturally occurring OA. Methods Enrollment in the OA group required a history of lameness,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 65 publications
1
7
1
Order By: Relevance
“…In the present study, MMP3 expression levels in both the low-and high-grade groups were significantly lower than those in the control group. These results differed from those of the human studies; however, there has been shown that MMP-3 levels were significantly lower in the synovial fluid of dogs with spontaneous OA than that of normal dogs [27]. Therefore, a part of the pathology in OA may be different between human and dogs.…”
Section: Plos Onecontrasting
confidence: 69%
“…In the present study, MMP3 expression levels in both the low-and high-grade groups were significantly lower than those in the control group. These results differed from those of the human studies; however, there has been shown that MMP-3 levels were significantly lower in the synovial fluid of dogs with spontaneous OA than that of normal dogs [27]. Therefore, a part of the pathology in OA may be different between human and dogs.…”
Section: Plos Onecontrasting
confidence: 69%
“…28 In dogs, increased levels IL-6, IL-8 and CCL2 have been associated with OA pain, although no correlation with radiographic OA severity or gait asymmetry was found. 29 30 31 The increase in inflammatory cytokines IL-7 and IL-15 during KJD in this study could be explained by increased catabolic activity during KJD, as is found during joint immobilization and midway KJD in experimental dogs. 32 However, in line with the clinical improvement observed, SF levels of IL-6, IL-8 and CCL2 decreased after KJD treatment.…”
Section: Discussionsupporting
confidence: 52%
“…To the best of our knowledge, this is the first study appraising synovial fluid after the administration of microfragmented adipose tissue in dogs. The cytological analysis of synovial fluid provides a qualitative measure of joint health, mainly associated with prognostic purposes [ 91 , 92 , 93 , 94 ]. In addition to the short-term cytological evaluation, the concentration of inflammatory cytokines in the synovial fluid was also evaluated.…”
Section: Discussionmentioning
confidence: 99%